General Municipal Ordinances of the City of Oakland, California 15, § 9 (1909) - (:unkn) unknown (My University, 1909)
Prohibited the carry of firearms, shooting of birds, or throwing of stones or other missiles within the boundaries of any park
Keywords: CARRY - CERTAIN PUBLIC PLACES